2019
DOI: 10.1128/iai.00255-18
|View full text |Cite
|
Sign up to set email alerts
|

Brucella neotomae Recapitulates Attributes of Zoonotic Human Disease in a Murine Infection Model

Abstract: Members of the genus Brucella are Gram-negative pathogens that cause chronic systemic infection in farm animals and zoonotic infection in humans. Study of the genus Brucella has been hindered by the need for biosafety level 3 select agent containment. Brucella neotomae, originally isolated from the desert pack rat, presented an opportunity to develop an alternative, non-select agent experimental model. Our prior in vitro work indicated that the cell biology and type IV secretion system (T4SS) dependence of B. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 50 publications
1
10
0
Order By: Relevance
“…The correct identification of this species was only possible by detailed phenotypic and genotypic analysis, including WGS [ 78 ]. After these reports, investigators confirmed the infective potential of B. neotomae in mice [ 80 , 81 ]. Another example of misidentification was the Brucella sp.…”
Section: Expanding the Number Of Brucella Specimentioning
confidence: 97%
“…The correct identification of this species was only possible by detailed phenotypic and genotypic analysis, including WGS [ 78 ]. After these reports, investigators confirmed the infective potential of B. neotomae in mice [ 80 , 81 ]. Another example of misidentification was the Brucella sp.…”
Section: Expanding the Number Of Brucella Specimentioning
confidence: 97%
“…Cell culture is widely used as a representative model for microorganism’s infectivity and is especially important in helping predict the range of pathogenicity of atypical Brucella species [16, 35–37]. Invasion and replication in epithelial cells and macrophages are vital in Brucella infections, although they are just one aspect to virulence [16, 37]. Other aspects important to virulence are the type IV secretion system and the LPS O-side chain [11, 13, 23, 35, 36].…”
Section: Discussionmentioning
confidence: 99%
“…melitensis , suggests that B . neotomae possesses the ability to behave in a similar manor to the classic virulent species [9,1216]. Since its discovery over 50 years ago B .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…B. neotomae, which natively infects desert pack rats, is highly related to select-agent Brucella species (B. melitensis, B. abortus, and B. suis) and also shares similar host cell infection dynamics and type IV secretion system-dependent intracellular replication and pathogenesis (5,13). However, in contrast to B. melitensis, B. abortus, and B. suis, it is not a select agent and is categorized as a biosafety level 2 pathogen, making it a useful model for highthroughput experiments.…”
mentioning
confidence: 99%